Pengaruh Buku Pendidikan Kesehatan Gigi Modern Interaktif Dengan Boneka Tangan Terhadap Pengetahuan Kesehatan Gigi Dan Mulut Anak Sekolah Dasar - Ibrahim, Rizal; Praptiwi, Yenni Hendriani; Supriyanto, Irwan; Widyastuti, Tri (Poltekkes Kemenkes Bandung, 2024)
Introduction : One of the factors causing suboptimal dental growth in children is tooth decay. This study aims to investigate the effect of the Hand Puppet Interactive Modern Dental Health Education Book on the knowledge improvement of third-grade students at SDN Harapan 212 in Bandung city. Method : This research employs a pre-experimental method with a pre-test and post-test design. The sample consists of 61 children selected using total sampling technique. Data analysis was conducted statistically using the Wilcoxon test. Results : The study revealed that before the introduction of the media, the average score of the students was 7.00 with a standard deviation of 0.22. However, after the media introduction, the average score increased to 15.00 with a standard deviation of 0.24. Statistical tests indicated a significant difference (p-value = 0.000 < 0.05) between the results before and after the intervention among the students of SDN Harapan 212 in Bandung city. Conclusion : The Hand Puppet Interactive Modern Dental Health Education Book significantly impacts the improvement of dental and oral health knowledge among elementary school children.